(untitled) (Research, Society and Development, 2023)
This article aims to question the relationship between the phenomena of immediate perception and those of mediate perception, which are more centered on memory and the past. If we make the hypothesis of spontaneous memory dependent on ontological memory, our object of study relates to the successions and qualities of psychic facts. To study this object, the initial reflection, on the proponents of the normal use of language in the Chomskian axis, aroused our curiosity about the problem of the qualities of each successive psychic fact. To retain that the mode of explanatory scientific reasoning is relevant by necessarily having to be supported by the experience of internal perception, our theoretical-methodological considerations are in this sense those of Bergson (1889; 1965; 1968) on duration and of Brentano (2008; 2017) on internal perception. The results of this research will contribute to the discovery of rules that relate, in the utterance, the syntactic structures with the representations of signified.